Implementation of business incubation program by PLUT KUMKM West Sumatera in Padang City - Annisa Yulia Zahra; Afriva Khaidir (Privietlab, 2025)
This study examines the implementation of the Business Incubation Program by PLUT KUMKM in Padang City, West Sumatra. Business incubation refers to a structured process involving guidance, mentoring, and business development provided by an incubator to support the growth of participating MSMEs. The research adopts George C. Edward III’s (1980) policy implementation model, which emphasizes four key variables that influence successfulimplementation : communication, resource, disposition, and bureaucratic structure. A qualitative descriptive approach was employed, with daya collected through in-depth interviews and documentation analyses. The research results show that the PLUT Business Incubation Program has met its objectives of providing guidance and assistance to MSMEs participating in the incubation. Support from agency leadership and the commitment of facilitators are reinforcing factors for implementation, while a clear organizational structure and the existence of SOPs support smooth execution of the program. Next, the factors influencing the Implementation of the Business Incubation Program by PLUT are: Supporting factors: leadership support, competence of implementers, adequate facilities, good internal coordination, and tangible benefits for participants. Inhibiting factors: Limited human resources and budget, uneven socialization, varying participant motivation, and lack of follow-up mentoring after the program. This study affirms that the PLUT KUMKM business incubation program plays an important role in enhancing the capacity and competitiveness of SMEs; however, it requires strengthening communication aspects, resources, and an implementation strategy that is more adaptive to the needs of SMEs business actors.